2020
DOI: 10.1016/j.meegid.2020.104534
|View full text |Cite
|
Sign up to set email alerts
|

The role of animals as a source of antimicrobial resistant nontyphoidal Salmonella causing invasive and non-invasive human disease in Vietnam

Abstract: Background Nontyphoidal Salmonella (NTS) are associated with both diarrhea and bacteremia. Antimicrobial resistance (AMR) is common in NTS in low-middle income countries, but the major source(s) of AMR NTS in humans are not known. Here, we aimed to assess the role of animals as a source of AMR in human NTS infections in Vietnam. We retrospectively combined and analyzed 672 NTS human and animal isolates from four studies in southern Vietnam and compared serovars, sequence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…*The total number of prevalence estimates was from 26 studies selected for meta-analyses of phenotypic AMR prevalence of NTS. Six studies conducted on humans with NTS diarrhea [ 20 , 22 , 25 , [69] , [70] , [71] ], 3 on invasive NTS infections [ 27 , 28 , 72 ], 2 studies on human with NTS enteric carriage [ 19 , 70 ], 12 studies in pigs [ 7 , 33 , 35 , 36 , 38 , 40 , 42 , 47 , 51 , 52 , 69 , 71 ], 9 studies in poultry [ 7 , 19 , 35 , 38 , 40 , 42 , 53 , 69 , 71 ], 6 studies on aquaculture [ 35 , 40 , 59 , 60 , 69 , 73 , 74 ] and 6 studies on cattle [ 35 , 40 , 42 , 58 , 69 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…*The total number of prevalence estimates was from 26 studies selected for meta-analyses of phenotypic AMR prevalence of NTS. Six studies conducted on humans with NTS diarrhea [ 20 , 22 , 25 , [69] , [70] , [71] ], 3 on invasive NTS infections [ 27 , 28 , 72 ], 2 studies on human with NTS enteric carriage [ 19 , 70 ], 12 studies in pigs [ 7 , 33 , 35 , 36 , 38 , 40 , 42 , 47 , 51 , 52 , 69 , 71 ], 9 studies in poultry [ 7 , 19 , 35 , 38 , 40 , 42 , 53 , 69 , 71 ], 6 studies on aquaculture [ 35 , 40 , 59 , 60 , 69 , 73 , 74 ] and 6 studies on cattle [ 35 , 40 , 42 , 58 , 69 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study characterizing sequence type and AMR patterns of NTS isolates from humans and animals indicated overlapping between sources. Accordingly, NTS in human blood were likely to have greater similarity (54%) to chicken isolates whereas NTS in human stools could be largely (40%) attributed to pig isolates [ 72 ]. In contrast, another study showed that S. typhimurium isolates from humans and animals (duck, pig and chicken) clustered into distinct clades in the phylogeny indicating limited evidence for the transmission of this pathogen [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Food safety is of global concern and the common serotypes identified in this study have been linked to human illness in Vietnam ( 69 , 70 ). In this study we used a collection of NTS from two studies of the pork value chain to understand the serotypes that are found on pork meat presented to customers, especially in context with increasing customer awareness and desire for safe food products.…”
Section: Discussionmentioning
confidence: 97%
“…One article provided a framework for any high-or low-income country in South or South-East Asia (SSEA) [21]. Twenty-four studies were designed in the context of specific countries , and four were sub-national [45][46][47][48]. Most national and sub-national studies were conducted in North American and European countries, but three studies originated from SSEA countries [35,46,47].…”
Section: Country Of Origin Publication Year and Study Typementioning
confidence: 99%